The Impact of Accountability-Oriented Control Aspects of Variance Investigation on Budgetary Slack and Moderating Effect of Moral Development - Deng, Deqiang; Liu, Lana Yan Jun; Wen, Subin (Frontiers in Psychology, 2020)
Variance investigation has been identified as an effective mechanism to reduce budgetary slack at ex-ante budgeting stage. This paper focuses on two further research questions: (1) the extent to which two different accountability-oriented control aspects (i.e. external investigation and self-reporting) of variance investigation impact on budgetary slack; and (2) the extent to which moderating effect of moral development places on the relationship between these two accountability-oriented control aspects and budgetary slack. Our experimental results show that both external investigation and self-reporting can reduce the propensity of creating slack at ex-ante budgeting stage. More specifically the effect of external investigation on reducing the propensity of creating budgetary slack is greater than that of self-reporting. This study further reveals that moral development moderates the effect of external investigation on budgetary slack. When comparing subordinates with low moral development with those with high moral development, our results show that the effect of external investigation on budgetary slack is stronger amongst the former group than the latter group. This study does not find any moderating effect of moral development on the relationship between self-reporting and budgetary slack. Our study sheds some new light on varying effects of two accountability-oriented control aspects of variance investigation on budgetary slack, which are also moderated by different levels of subordinates’ moral development. These results may be considered in the design and implementation of management control systems.